Myastenia gravis following H1N1 infection - Silva, Horta e; Nascimento, A.; Zwolinski, N.; André, A. (Journal of the Portuguese Society of Anesthesiology, 2016)
Introduction: Myasthenia gravis is an auto-immune disease, resulting from the production of anti-Ach receptor antibodies at the neuromuscular junction. In spite of its unknown etiology, there seems to exist some factors which withstand its arise and/or the worsening of the patient's clinical condition. The mainstay of medical treatment relies on anticholinesterase drugs and immunosuppression. Thymectomy is considered the treatment of choice in selected cases. Influenza A (H1N1) viral infection was considered the disease’s triggering factor in this case, so far never reported. Clinical Report: Female patient, 49 years old, with a previous history of arterial hypertension, obesity and Influenza A (H1N1) viral infection, with subsequent development of an acute respiratory distress syndrome. Three months after the infection, the patient presents an inaugural myasthenic crisis with progressive deterioration. Medical therapy was immediately undertaken, including the administration of supplemental oxygen and institution of non-invasive mechanical ventilation....